Impact of Hippocratic medicine on the development of disease observation and prevention in modern medical practice - Cedeño, Doménica; Chimbo, Ámbar; Zambrano, Pierina (Revista Gregoriana de Ciencias de la Salud, 2024)
The healing practice originating in Hippocratic Medicine has always been linked to human beings. Assisting the afflicted is a fundamental medical action. The basic principles of Hippocrates, such as the doctor-patient relationship and disease prevention, have been pillars in the training of doctors. The objective of this essay was to analyze the importance of Hippocratic medicine in the observation and prevention of diseases, and its relationship with current medicine. Currently, the trend toward extreme specialization limits comprehensive care and deep understanding of the patient's condition. The influence of Hippocratic medicine on modern practice has diminished, allowing the development of a mechanistic and materialist vision incompatible with the Hippocratic tradition, which forgot the holistic approach and the idea of treating sick people, not diseases.